PATRIOTIC FEELINGS IN THE ATTITUDES OF DAGESTAN PEOPLE - Sahbanova, M M (History, Archeology and Ethnography of the Caucasus, 2016)
The article covers the phenomenon of patriotism and patriotic feelings in the mass consciousness of the peoples of Dagestan. The author determines that Russian identity dominates over other types of social identity, and this fact depends on the degree of development of patriotic feelings in the society and is closely connected with patriotism. The results of the study show that indices of patriotism are love of the motherland, pride in the country, desire to improve life in the country, readiness to act for its well-being, a sense of responsibility for what is happening in the country, besides, the patriotic feelings are expressed by worldview and moral attitudes and ideas